Polylactic acid composite film with high heat resistance and puncture resistance and preparation method thereof

High-purity stereotactic polylactic acid microspheres are prepared through thermal phase separation process and non-solvent phase separation process, and surface modification and carboxylation are carried out, which solves the problem that PLA is limited by its performance in some fields, and achieves the high heat resistance and puncture resistance of polylactic acid composite films.

CN119552396APending Publication Date: 2025-03-04NINGBO POLYTECHNIC
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411915034.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The application of polylactic acid (PLA) in certain fields is limited by its poor tensile strength, toughness, heat resistance and puncture resistance.

Method used

High-purity stereotactic polylactic acid microspheres were prepared by thermally induced phase separation process and non-solvent phase separation process, and the surface of the microspheres was silane modified, and the surface of the microcrystalline cellulose was carboxylated to improve their dispersion and compatibility in the PLA matrix.

Benefits of technology

The crystallization, heat resistance and puncture resistance of the polylactic acid composite film are significantly improved, and a PLA composite film with high heat resistance and puncture resistance is formed.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119552396A_ABST
    Figure CN119552396A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of polymer films, and relates to a highly heat-resistant puncture-resistant polylactic acid composite film and a preparation method thereof, and the preparation method comprises the following steps: preparing high-purity stereopolylactic acid microspheres by using a thermally induced phase separation process and a non-solvent phase separation process, and carrying out silane modification on the surfaces of the stereopolylactic acid microspheres to obtain modified stereopolylactic acid microspheres (msc-PLA); msc-PLA, microcrystalline cellulose and polylactic acid are prepared into the polylactic acid composite film through a solution pouring method. The msc-PLA is used as the nucleating agent, and the microcrystalline cellulose is used as the reinforcing agent, so that the crystallization property, heat resistance and puncture resistance of the polylactic acid film are effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer films, and in particular relates to a highly heat-resistant and puncture-resistant polylactic acid composite film and a preparation method thereof. Background Art

[0002] Plastics are widely used in food packaging, medical devices, electronic appliances and other fields due to their light weight, easy processing and low cost. As one of the three major polymer materials, plastics have an average annual growth rate of 8.7% and an annual output of more than 335 million tons. Among them, packaging materials such as bottles and films account for the largest proportion and are the main culprits of environmental pollution. Since plastics are mainly extracted from petroleum and are non-renewable, it is urgent to develop renewable, degradable and environmentally friendly materials.

[0003] Polylactic acid (PLA) is a polyester polymer material, which is mainly obtained by polymerizing lactic acid (LA) extracted from crops such as straw, corn, and wheat. It can be completely degraded into water and carbon dioxide. It is currently the most promising biodegradable material and is widely used in food packaging, medical and health care, textile products and other fields. However, there are still some problems with PLA, which limit its application in certain fields. Specifically, they include: (1) PLA has a semi-rigid chain structure and is difficult to crystallize under normal conditions, resulting in poor tensile strength and toughness of PLA, which cannot meet high-strength usage scenarios; (2) PLA crystallization rate is slow, and the processing process is usually amorphous, which makes PLA heat resistance poor, and the heat deformation temperature is only about 60°C; (3) Due to the low mechanical strength of PLA, PLA film has poor puncture resistance, which limits its application in the field of biofilms.

[0004] At present, the main methods for enhancing and modifying PLA include: adding nucleating agents, blending modification, optimizing molding process and annealing treatment, among which adding nucleating agents is the most efficient and convenient method for modifying PLA. Nucleating agents mainly include inorganic nucleating agents, organic nucleating agents, bio-based nucleating agents, etc. Among them, bio-based nucleating agents have the advantages of good compatibility with PLA, high nucleation efficiency, and complete degradation, and are currently a hot research topic. Stereopolylactic acid is a polymer with a specific crystal form formed by left-handed polylactic acid and right-handed polylactic acid under the action of hydrogen bonds. It has high mechanical strength and excellent heat resistance and is an excellent bio-based nucleating agent for PLA. However, high-purity stereopolylactic acid is difficult to obtain under normal conditions. In most cases, it is a mixed crystal formed by homogeneous polylactic acid and stereopolylactic acid. For example, the patent with application number CN202210242747.2 discloses a method for preparing fully stereoscopic polylactic acid microspheres, by using amphiphilic solid stabilizer particles to encapsulate a L-polylactic acid / D-polylactic acid complex to obtain stereoscopic polylactic acid microspheres with a stable heat-resistant structure. The patent with application number CN201910679645.5 discloses a fully stereoscopic polylactic acid porous microsphere and a method for preparing the same, by dissolving PLLA and PDLA in a solvent and cooling the polylactic acid solution to a specific temperature to obtain polylactic acid microspheres having a fully stereoscopic crystal morphology and a porous structure. However, the stereoscopic polylactic acid microspheres prepared by the prior art have problems such as complex preparation process, wide distribution of microsphere particle size, and low stereocrystalline content, and cannot give full play to the advantages of stereoscopic polylactic acid as a bio-based nucleating agent. Summary of the invention

[0005] In view of the above-mentioned shortcomings of the prior art, an object of the present invention is to provide a highly heat-resistant and puncture-resistant polylactic acid composite film and a preparation method thereof.

[0006] In order to achieve the above-mentioned object and other related objects, the present invention provides the following technical solutions: In a first aspect, a method for preparing a highly heat-resistant and puncture-resistant polylactic acid composite film is provided, comprising the following steps: Weighing left-handed polylactic acid (PLLA) and right-handed polylactic acid (PDLA), drying and adding them to the mixed dibasic acid ester, transferring the solution to an oil bath, heating, stirring until the polylactic acid is completely dissolved, adding silane, continuing to stir, adding an extractant, stirring, cooling, separating, washing, and drying to obtain microspheres, namely msc-PLA; Weigh microcrystalline cellulose (MCC), add it to the sulfuric acid solution, transfer the solution to a water bath, stir it thoroughly, and filter it under reduced pressure to obtain surface-modified microcrystalline cellulose, i.e., m-MCC; msc-PLA, m-MCC, L-polylactic acid and D-polylactic acid are added to an organic solvent, fully stirred, uniformly poured into a glass culture dish, allowed to stand, and dried to obtain a polylactic acid composite film.

[0007] In one embodiment, the temperature is raised to 80-120°C.

[0008] In one embodiment, the sulfuric acid solution is a concentrated sulfuric acid solution.

[0009] In one embodiment, the added amount of L-polylactic acid and D-polylactic acid is 2-5 g; the added ratio of L-polylactic acid to D-polylactic acid is 1:1.

[0010] In one embodiment, the mixed dibasic acid ester includes one or more of dimethyl succinate, dimethyl glutarate, and dimethyl adipate.

[0011] In one embodiment, the silane includes one or more of aminopropyltriethoxysilane, tetraethoxysilane, and methyltrimethoxysilane.

[0012] In one embodiment, the amount of silane added is 0.04-0.1 g.

[0013] In one embodiment, the extractant includes one or more of dioctyl phosphate, tributyl phosphate, and trioctyl tertiary amine.

[0014] In one embodiment, the added amount of msc-PLA is 0.01-0.05 g.

[0015] In one embodiment, the added amount of m-MCC is 0.5-2 g.

[0016] In one embodiment, the organic solvent includes one or more of dichloromethane, chloroform, and N,N-dimethylformamide (DMF).

[0017] In one embodiment, the left-handed polylactic acid includes one or more of Total Corbivir LX175, Total Corbivir LX530, and Total Corbivir LX930; the right-handed polylactic acid includes one or more of Total Corbivir D070 and Total Corbivir D120; and the microcrystalline cellulose brand includes one or more of MFC-50, MFC-100, and MFC-200 of Shandong Lusen Biotechnology Co., Ltd.

[0018] It should be noted that, by adopting the above-mentioned technical scheme, the present invention utilizes a thermally induced phase separation process and a non-solvent phase separation process to prepare high-purity stereopolymeric polylactic acid microspheres, and performs silane modification on the surface of the microspheres to improve the dispersibility of the stereopolymeric polylactic acid microspheres in the PLA matrix. In addition, the MCC is subjected to a surface carboxylation treatment to further improve the dispersibility and compatibility of the reinforcing agent in the PLA matrix, thereby obtaining a PLA composite film with high heat resistance and puncture resistance.

[0019] In a second aspect, a highly heat-resistant and puncture-resistant polylactic acid composite film is provided, which is prepared by the aforementioned method.

[0020] The beneficial effects of the present invention are: (1) In the prior art, phase separation methods include non-solvent induced phase separation (NIPS) and thermally induced phase separation (TIPS), and one of them is generally selected to make a thin film with a porous structure. However, the present invention innovatively introduces two phase separation methods at the same time. This has certain technical difficulties. The TIPS process relies on temperature changes to drive the phase separation of solvent and polymer, while the NIPS process relies on the mixed interaction of solvent and non-solvent. The driving forces of these two processes are different, and the process parameters (such as solvent selection, non-solvent ratio, temperature control, etc.) are all technical difficulties. The introduction of two phase separation behaviors at the same time is prone to unstable phase separation behaviors, which may cause competition effects, making the microsphere morphology difficult to control and affecting its shape and distribution.

[0021] However, the present invention successfully prepares stereopolymeric polylactic acid microspheres with high purity and narrow particle size distribution through thermally induced phase separation process and non-solvent phase separation process.

[0022] (2) Silane modification of the surface of stereopolymeric polylactic acid microspheres can effectively improve the dispersibility of the microspheres in PLA.

[0023] (3) The MCC surface was carboxylated to effectively improve the compatibility of MCC with msc-PLA and PLA matrix, and significantly improve the puncture resistance of PLA composite film.

[0024] In general, the present invention uses msc-PLA as a nucleating agent and modified MCC as a reinforcing agent, which effectively improves the crystallization performance, heat resistance and puncture resistance of the polylactic acid film, and the finished product has a better morphology. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. They are used to explain the present invention together with the embodiments of the present invention and do not constitute a limitation of the present invention.

[0026] In the attached picture: Figure 1 It is a schematic diagram of a process of a highly heat-resistant and puncture-resistant polylactic acid composite film and a preparation method according to an embodiment of the present invention.

[0027] Figure 2 This is an SEM image of the stereostructured polylactic acid microspheres of Example 1 of the present invention; it should be noted that, in the figure, Mag (magnification) = 5.00KX, EHT (acceleration voltage) = 5.00kV, WD (working distance) = 5.1mm, SignalA (secondary electron detector) = SE2.

[0028] Figure 3This is the XRD diagram of the stereopolymeric polylactic acid microspheres of Example 1 of the present invention. It should be noted that 12.0°, 20.9°, and 24.2° correspond to the crystal planes of the (110), (300), and (220) triclinic systems of the stereopolymeric polylactic acid microspheres, respectively, and are characteristic diffraction peaks of the stereopolymeric polylactic acid microspheres.

[0029] Figure 4 This is the DSC graph of stereopolymeric polylactic acid microspheres of Example 1 of the present invention.

[0030] Figure 5 It is a macroscopic schematic diagram of the polylactic acid composite film prepared in an embodiment of the present invention.

[0031] It should be noted that the stereopolymeric polylactic acid microspheres mentioned above are msc-PLA. DETAILED DESCRIPTION

[0032] The applicant will describe the embodiments of the present invention in detail below. It should be noted that the embodiments described below are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention. In addition, if not otherwise specified, all reagents used in the following embodiments are commercially available or can be synthesized with reference to existing literature or known methods, and for the reactions or test conditions not listed, they are also the conventional techniques that are easily available to those skilled in the art. The terms used in the present invention are general in the art, and those skilled in the art can clearly understand their meanings, such as, solution, decompression, drying, pouring, etc., and will not be repeated one by one.

[0033] The present invention provides a highly heat-resistant and puncture-resistant polylactic acid composite film and a preparation method thereof, referring to Figure 1 The flow chart was prepared.

[0034] Among them, L-polylactic acid LX175, L-polylactic acid LX530, and L-polylactic acid LX930 are all from Total Cobiene; D-polylactic acid D070 and D-polylactic acid D120 are both from Total Cobiene.

[0035] The brand of microcrystalline cellulose is one or more of MFC-50, MFC-100 and MFC-200 produced by Shandong Lusen Biotechnology Co., Ltd.

[0036] Example 1 Step 1: Weigh 2g of left-handed polylactic acid LX175 and 2g of right-handed polylactic acid D070, dry them in an 80℃ blast drying oven for 24h, then add them to 100mL of dimethyl succinate, transfer the solution to an oil bath with a 250mL single-necked flask, heat to 110℃, stir magnetically for 2h until the polylactic acid is completely dissolved, add 0.04g of aminopropyltriethoxysilane, continue stirring for 2h, immediately add 10mL of diisooctyl phosphate, stir for 10min, transfer the solution to a 5℃ low-temperature explosion-proof refrigerator and cool naturally, centrifuge the product, wash it 3 times with ethanol, and fully dry it in a 60℃ blast drying oven to obtain msc-PLA-1 microspheres. Its morphology can be referred to Figure 2 .

[0037] Step 2: Weigh 2 g of microcrystalline cellulose MFC-50 and add it to 100 mL of concentrated sulfuric acid solution (52 wt%). Transfer the solution to a water bath with a 250 mL single-necked flask, stir it thoroughly at 50 °C for 30 min, and filter it under reduced pressure to obtain surface-modified microcrystalline cellulose m-MCC-1.

[0038] Step 3: Add 0.01g of msc-PLA-1 microspheres, 0.5g of m-MCC-1, 2g of L-polylactic acid LX175 and 2g of D-polylactic acid D070 to 100mL of dichloromethane, stir thoroughly at room temperature for 24h, pour evenly into a glass culture dish, place it in a fume hood for 12h, and then transfer it to a 40℃ forced air drying oven to fully dry to obtain a polylactic acid composite film. Figure 2-5 .

[0039] Example 2 Step 1: Weigh 3 g of left-handed polylactic acid LX530 and 3 g of right-handed polylactic acid D070, dry them in an 80°C air drying oven for 24 h, then add them to 100 mL of dimethyl glutarate, transfer the solution to an oil bath with a 250 mL single-necked flask, heat to 110°C, and stir magnetically for 2 h until the polylactic acid is completely dissolved, add 0.06 g of tetraethoxysilane, continue stirring for 2 h, immediately add 10 mL of tributyl phosphate, stir for 10 min, transfer the solution to a 5°C low-temperature explosion-proof refrigerator for natural cooling, centrifuge the product, wash it three times with ethanol, and fully dry it in a 60°C air drying oven to obtain msc-PLA-2 microspheres.

[0040] Step 2: Weigh 2 g of microcrystalline cellulose MFC-100 and add it to 100 mL of concentrated sulfuric acid solution (52 wt%). Transfer the solution to a water bath with a 250 mL single-necked flask, stir it thoroughly at 50 °C for 30 min, and filter it under reduced pressure to obtain surface-modified microcrystalline cellulose m-MCC-2.

[0041] Step 3: Add 0.02g of msc-PLA-2 microspheres, 0.8g of m-MCC-2, 3g of L-polylactic acid LX175 and 3g of D-polylactic acid D070 to 100mL of chloroform, stir thoroughly at room temperature for 24h, evenly pour into a glass culture dish, place in a fume hood for 12h, and then transfer to a 40℃ forced air drying oven to fully dry to obtain a polylactic acid composite film. Figure 5 .

[0042] Example 3 Step 1: Weigh 4 g of left-handed polylactic acid LX930 and 4 g of right-handed polylactic acid D120, dry them in an 80°C air drying oven for 24 h, then add them to 100 mL of dimethyl adipate, transfer the solution to an oil bath with a 250 mL single-necked flask, heat to 110°C, and stir magnetically for 2 h until the polylactic acid is completely dissolved, add 0.08 g of methyltrimethoxysilane, continue stirring for 2 h, immediately add 10 mL of trioctyl tertiary amine, stir for 10 min, transfer the solution to a 5°C low-temperature explosion-proof refrigerator for natural cooling, centrifuge the product, wash it three times with ethanol, and fully dry it in a 60°C air drying oven to obtain msc-PLA-3 microspheres.

[0043] Step 2: Weigh 2 g of microcrystalline cellulose MFC-200 and add it to 100 mL of concentrated sulfuric acid solution (52 wt%). Transfer the solution to a water bath with a 250 mL single-necked flask, stir it thoroughly at 50 °C for 30 min, and filter it under reduced pressure to obtain surface-modified microcrystalline cellulose m-MCC-3.

[0044] Step 3: Add 0.03 g of msc-PLA-3 microspheres, 1.0 g of m-MCC-3, 4 g of L-polylactic acid LX175 and 4 g of D-polylactic acid D120 to 100 mL of N,N-dimethylformamide, stir thoroughly at room temperature for 24 h, pour evenly into a glass culture dish, place in a fume hood for 12 h, and then transfer to a 40°C forced air drying oven to fully dry to obtain a polylactic acid composite film. Figure 5 .

[0045] Example 4 Step 1: Weigh 5 g of left-handed polylactic acid LX530 and 5 g of right-handed polylactic acid D120, dry them in an 80°C air drying oven for 24 h, then add them to 100 mL of dimethyl glutarate, transfer the solution to an oil bath with a 250 mL single-necked flask, heat to 110°C, and stir magnetically for 2 h until the polylactic acid is completely dissolved, add 0.1 g of tetraethoxysilane, continue stirring for 2 h, immediately add 10 mL of tributyl phosphate, stir for 10 min, transfer the solution to a 5°C low-temperature explosion-proof refrigerator for natural cooling, centrifuge the product, wash it three times with ethanol, and fully dry it in a 60°C air drying oven to obtain msc-PLA-4 microspheres.

[0046] Step 2: Weigh 2 g of microcrystalline cellulose MFC-100 and add it to 100 mL of concentrated sulfuric acid solution (52 wt%). Transfer the solution to a water bath with a 250 mL single-necked flask, stir it thoroughly at 50 °C for 30 min, and filter it under reduced pressure to obtain surface-modified microcrystalline cellulose m-MCC-2.

[0047] Step 3: Add 0.04 g of msc-PLA-4 microspheres, 1.6 g of m-MCC-2, 5 g of L-polylactic acid LX175 and 5 g of D-polylactic acid D120 to 100 mL of chloroform, stir thoroughly at room temperature for 24 h, evenly pour into a glass culture dish, place in a fume hood for 12 h, and then transfer to a 40°C forced air drying oven to fully dry to obtain a polylactic acid composite film. Figure 5 .

[0048] Example 5 Step 1: Weigh 5 g of left-handed polylactic acid LX175 and 5 g of right-handed polylactic acid D070, dry them in an 80°C air drying oven for 24 h, then add them to 100 mL of dimethyl succinate, transfer the solution to an oil bath with a 250 mL single-necked flask, heat to 110°C, and stir magnetically for 2 h until the polylactic acid is completely dissolved, add 0.1 g of aminopropyltriethoxysilane, continue stirring for 2 h, immediately add 10 mL of diisooctyl phosphate, stir for 10 min, transfer the solution to a 5°C low-temperature explosion-proof refrigerator for natural cooling, centrifuge the product, wash it three times with ethanol, and fully dry it in a 60°C air drying oven to obtain msc-PLA-5 microspheres.

[0049] Step 2: Weigh 2 g of microcrystalline cellulose MFC-50 and add it to 100 mL of concentrated sulfuric acid solution (52 wt%). Transfer the solution to a water bath with a 250 mL single-necked flask, stir it thoroughly at 50 °C for 30 min, and filter it under reduced pressure to obtain surface-modified microcrystalline cellulose m-MCC-1.

[0050] Step 3: Add 0.05 g of msc-PLA-5 microspheres, 2.0 g of m-MCC-1, 5 g of L-polylactic acid LX175 and 5 g of D-polylactic acid D070 to 100 mL of dichloromethane, stir thoroughly at room temperature for 24 h, evenly pour into a glass culture dish, place in a fume hood for 12 h, and then transfer to a 40°C forced air drying oven to fully dry to obtain a polylactic acid composite film. Figure 5 .

[0051] Comparative Example 1 Step 1: Weigh 2 g of microcrystalline cellulose MFC-50 and add it to 100 mL of concentrated sulfuric acid solution (52 wt%). Transfer the solution to a water bath with a 250 mL single-necked flask, stir it thoroughly at 50 °C for 30 min, and filter it under reduced pressure to obtain surface-modified microcrystalline cellulose m-MCC-1.

[0052] Step 2: Add 0.5 g of m-MCC-1, 2 g of left-handed polylactic acid LX175 and 2 g of right-handed polylactic acid D070 to 100 mL of dichloromethane, stir thoroughly at room temperature for 24 h, pour evenly into a glass culture dish, place it in a fume hood for 12 h, and then transfer it to a 40°C forced air drying oven for thorough drying to obtain a polylactic acid composite film.

[0053] It should be noted that microspheres were not prepared in this comparative example.

[0054] Comparative Example 2 Step 1: Weigh 3 g of left-handed polylactic acid LX530 and 3 g of right-handed polylactic acid D070, dry them in an 80°C air drying oven for 24 h, then add them to 100 mL of dimethyl glutarate, transfer the solution to an oil bath with a 250 mL single-necked flask, heat to 110°C, and stir magnetically for 2 h until the polylactic acid is completely dissolved, immediately add 10 mL of tributyl phosphate, stir for 10 min, transfer the solution to a 5°C low-temperature explosion-proof refrigerator for natural cooling, centrifuge the product, wash it three times with ethanol, and fully dry it in a 60°C air drying oven to obtain sc-PLA-2 microspheres.

[0055] Step 2: Weigh 2 g of microcrystalline cellulose MFC-100 and add it to 100 mL of concentrated sulfuric acid solution (52 wt%). Transfer the solution to a water bath with a 250 mL single-necked flask, stir it thoroughly at 50 °C for 30 min, and filter it under reduced pressure to obtain surface-modified microcrystalline cellulose m-MCC-2.

[0056] Step 3: Add 0.02 g of sc-PLA-2 microspheres, 0.8 g of m-MCC-2, 3 g of left-handed polylactic acid LX530 and 3 g of right-handed polylactic acid D070 to 100 mL of chloroform, stir thoroughly at room temperature for 24 h, pour evenly into a glass culture dish, place in a fume hood for 12 h, and then transfer to a 40°C forced air drying oven for thorough drying to obtain a polylactic acid composite film.

[0057] It should be noted that in this comparative example, the preparation method of the microspheres is different.

[0058] Comparative Example 3 Step 1: Weigh 4 g of left-handed polylactic acid LX930 and 4 g of right-handed polylactic acid D120, dry them in an 80°C air drying oven for 24 h, then add them to 100 mL of dimethyl adipate, transfer the solution to an oil bath with a 250 mL single-necked flask, heat to 110°C, and stir magnetically for 2 h until the polylactic acid is completely dissolved, add 0.08 g of methyltrimethoxysilane, continue stirring for 2 h, immediately add 10 mL of trioctyl tertiary amine, stir for 10 min, transfer the solution to a 5°C low-temperature explosion-proof refrigerator for natural cooling, centrifuge the product, wash it three times with ethanol, and fully dry it in a 60°C air drying oven to obtain msc-PLA-3 microspheres.

[0059] Step 2: Add 0.03 g of msc-PLA-3 microspheres, 4 g of left-handed polylactic acid LX930 and 4 g of right-handed polylactic acid D120 to 100 mL of N,N-dimethylformamide, stir thoroughly at room temperature for 24 h, pour evenly into a glass culture dish, place it in a fume hood for 12 h, and then transfer it to a 40°C forced air drying oven for thorough drying to obtain a polylactic acid composite film.

[0060] It should be noted that in this comparative example, no surface-modified microcrystalline cellulose or microcrystalline cellulose was added.

[0061] Comparative Example 4 Step 1: Weigh 5 g of left-handed polylactic acid LX530 and 5 g of right-handed polylactic acid D120, dry them in an 80°C air drying oven for 24 h, then add them to 100 mL of dimethyl glutarate, transfer the solution to an oil bath with a 250 mL single-necked flask, heat to 110°C, and stir magnetically for 2 h until the polylactic acid is completely dissolved, add 0.1 g of tetraethoxysilane, continue stirring for 2 h, immediately add 10 mL of tributyl phosphate, stir for 10 min, transfer the solution to a 5°C low-temperature explosion-proof refrigerator for natural cooling, centrifuge the product, wash it three times with ethanol, and fully dry it in a 60°C air drying oven to obtain msc-PLA-4 microspheres.

[0062] Step 2: Add 0.04 g of msc-PLA-4 microspheres, 1.6 g of MFC-100, 5 g of left-handed polylactic acid LX530 and 5 g of right-handed polylactic acid D120 to 100 mL of chloroform, stir thoroughly at room temperature for 24 h, pour evenly into a glass culture dish, place in a fume hood for 12 h, and then transfer to a 40°C forced air drying oven for thorough drying to obtain a polylactic acid composite film.

[0063] It should be noted that, although microcrystalline cellulose was added in this comparative example, the microcrystalline cellulose was not modified, that is, surface-modified microcrystalline cellulose was not added.

[0064] Detection: The evaluation results of Examples 1-5 and Comparative Examples 1-4 are shown in Table 1.

[0065] Table 1 Evaluation results of polylactic acid composite films obtained in various examples and comparative examples

[0066] in: The tensile strength and elongation at break were tested according to ASTM D882 at a tensile rate of 50 mm / min.

[0067] Heat deformation temperature (HDT) was measured according to GB / T 1634-2004, with a load of 0.45 MPa, preheating for 3 min, and a heating rate of 2 °C / min.

[0068] The puncture strength is measured according to ASTM D 4833-2007. During the test, the film sample is first fixed on a fixture with a diameter of 45 mm, and a spherical probe with a diameter of 0.5 mm is used to pierce the film at a speed of 10 cm / min, and the puncture force is recorded.

[0069] Analysis: No microspheres are added in Comparative Example 1. It can be seen from Example 1 and Comparative Example 1 that the present invention can effectively improve the mechanical strength and heat deformation temperature of the PLA composite film by introducing msc-PLA, and has a certain promoting effect on the improvement of the puncture resistance; The preparation method of the microspheres in Comparative Example 2 is different. It can be seen from Example 2 and Comparative Example 2 that silane modification of the surface of stereopolymeric polylactic acid microspheres can effectively improve the mechanical strength and heat deformation temperature of the PLA composite film, but there is no significant improvement in the puncture resistance; In Comparative Example 3, surface-modified microcrystalline cellulose or microcrystalline cellulose is not added. It can be seen from Example 3 and Comparative Example 3 that the introduction of carboxyl-modified MCC can effectively improve the puncture resistance of the PLA composite film, and at the same time, the mechanical strength and heat deformation temperature are improved to a certain extent; Although microcrystalline cellulose is added in Comparative Example 4, the microcrystalline cellulose is not modified, that is, surface-modified microcrystalline cellulose is not added. It can be seen from Example 4 and Comparative Example 4 that carboxylation modification of MCC can further improve the puncture resistance of the PLA composite film; It can be seen from Example 4 and Comparative Example 4 that after adding unmodified MCC, the tensile strength of the PLA composite film is reduced, indicating that the unmodified MCC has a negative impact on the mechanical strength of the PLA composite film.

[0070] In addition, through Figure 2-Figure 5 It can be seen that the stereopolymeric polylactic acid microspheres prepared by the present invention have a better morphology, which overcomes the technical difficulties that would occur when two phase separation methods are used simultaneously.

[0071] The surface of the finished composite film is smooth, flat and uniform.

[0072] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention is described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a highly heat-resistant and puncture-resistant polylactic acid composite film, characterized in that: The steps include: Weigh left-handed polylactic acid and right-handed polylactic acid, dry them and add them to the mixed dibasic acid ester, transfer the solution to an oil bath, heat it up, stir until the polylactic acid is completely dissolved, add silane, continue stirring, add an extractant, stir, cool, separate, wash, and dry to obtain microspheres, i.e., msc-PLA; Weigh microcrystalline cellulose, add it to the sulfuric acid solution, transfer the solution to a water bath, stir it thoroughly, and filter it under reduced pressure to obtain surface-modified microcrystalline cellulose, i.e., m-MCC; msc-PLA, m-MCC, L-polylactic acid and D-polylactic acid are added to an organic solvent, fully stirred, uniformly poured into a glass culture dish, allowed to stand, and dried to obtain a polylactic acid composite film.

2. The method for preparing a highly heat-resistant and puncture-resistant polylactic acid composite film according to claim 1, characterized in that: The added amounts of L-polylactic acid and D-polylactic acid are both 2-5 g; the added ratio of L-polylactic acid to D-polylactic acid is 1:

1.

3. The method for preparing a highly heat-resistant and puncture-resistant polylactic acid composite film according to claim 1, characterized in that: The mixed dibasic acid ester includes one or more of dimethyl succinate, dimethyl glutarate and dimethyl adipate.

4. The method for preparing a highly heat-resistant and puncture-resistant polylactic acid composite film according to claim 1, characterized in that: The silane includes one or more of aminopropyltriethoxysilane, tetraethoxysilane and methyltrimethoxysilane.

5. The method for preparing a highly heat-resistant and puncture-resistant polylactic acid composite film according to claim 1, characterized in that: The amount of silane added is 0.04-0.1g.

6. The method for preparing a highly heat-resistant and puncture-resistant polylactic acid composite film according to claim 1, characterized in that: The extractant includes one or more of diisooctyl phosphate, tributyl phosphate, and trioctyl tertiary amine.

7. The method for preparing a highly heat-resistant and puncture-resistant polylactic acid composite film according to claim 1, characterized in that: The added amount of msc-PLA is 0.01-0.05g.

8. The method for preparing a highly heat-resistant and puncture-resistant polylactic acid composite film according to claim 1, characterized in that: The amount of m-MCC added is 0.5-2g.

9. The method for preparing a highly heat-resistant and puncture-resistant polylactic acid composite film according to claim 1, characterized in that: The organic solvent includes one or more of dichloromethane, chloroform, and N,N-dimethylformamide.

10. The method for preparing a highly heat-resistant and puncture-resistant polylactic acid composite film according to claim 1, characterized in that: The left-handed polylactic acid includes one or more of Total Corbivir LX175, Total Corbivir LX530, and Total Corbivir LX930; the right-handed polylactic acid includes one or more of Total Corbivir D070 and Total Corbivir D120; the microcrystalline cellulose includes one or more of Shandong Lusen Biotechnology Co., Ltd. MFC-50, Shandong Lusen Biotechnology Co., Ltd. MFC-100, and Shandong Lusen Biotechnology Co., Ltd. MFC-200; when heating, the temperature is raised to 80-120°C.

Citation Information

Patent Citations

  • A fully stereolithographic polylactic acid porous microsphere and its preparation method

    CN110624484B

  • All-stereo polylactic acid microsphere with stable heat-resistant structure and preparation method of all-stereo polylactic acid microsphere

    CN114736403A